The Concept of Morals in the Works of Lithuanian Neo-Thomists - Burnys, Z. (Problemos, 1978)
The article presents a critical analysis of the concept of morals and ethics in the works of the Lithuanian Neo-Thomists J. Česaitis, P. Dovydaitis, A. Jakštas-Dambrauskas, P. Kuraitis, A. Maliauskis and others in 1920-1940. Attempts of the representatives of Neo-Thomism to establish the governing role of Catholic ethics are pointed out. Explanation of the origins of moral codes and the contents of definite principles and values of morals are discussed in detail. The Neo-Thomist treatment of the above problems is compared with their interpretation in the social methodology of Marxism.